International economics - Gerber, James (Boston : Addison-Wesley, 2005)
International Economics is a lively introduction to the study of international trade and finance. Built on a theoretical framework emphasizing the central concepts, this book uses a rich array of case studies to illuminate economic institutions and policies as well as recent developments in the global economy
Includes bibliographical references (p. 449-458) and index.
obn 02/10/2018
Loans
Keywords: International economic relations; International economic integration; International trade; Commercial policy; United States